2018
DOI: 10.1055/s-0038-1675369
|View full text |Cite
|
Sign up to set email alerts
|

The First Dorsal Metacarpal Artery Flap Family: A Review

Abstract: Deep soft tissue injuries around the thumb can severely hinder hand function if not treated correctly. Many different surgical options have been described for the treatment of these serious lesions, including microsurgical flaps, such as toe to hand flaps, local flaps, and distant pedicled flaps. The first dorsal metacarpal artery family of flaps belongs to this last category. These flaps can be performed in different ways, as a racquet, as an island flap, and as a bilobed flap including the second metacarpal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…On the other hand, local flaps offer advanced esthetic result as the defect is replaced by "similar" tissue. Especially the DMA flaps outmatch as they offer extra amount of soft tissue availability [3,6,9,[17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, local flaps offer advanced esthetic result as the defect is replaced by "similar" tissue. Especially the DMA flaps outmatch as they offer extra amount of soft tissue availability [3,6,9,[17][18].…”
Section: Resultsmentioning
confidence: 99%
“…Several reconstructive options such as local, regional and free flap transfers have been used including the dorsal metacarpal artery (DMA) flaps [2][3][4]. In particular, the use of the first DMA flap has been widely reported in the indexed literature for the repair of deep soft tissue defects of the thumb [5][6][7][8][9]. However, one of the drawbacks of this flap is related to donor site morbidity, since the donor site defect which remains on the dorsum of the index finger, requires skin graft for coverage from a second donor site [10].…”
Section: Introductionmentioning
confidence: 99%
“…The former often requires prolonged immobilization, rehabilitation, and hospitalization. Therefore, a variety of regional flaps based on the dorsal metacarpal arteries (DMCAs) became popular in the 1990s (Couceiro et al, ). These flaps are all useful; however, the donor site requires skin grafts if the flap is large and the appearance is unaesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a variety of regional flaps based on the dorsal metacarpal arteries (DMCAs) became popular in the 1990s (Couceiro et al, 2018).…”
mentioning
confidence: 99%
“…reported that in their cadaver study, the third and fourth DMAs were not observed in 3% and 14% of the cadavers, respectively. Sebastin et al [5] and Couceiro et al [15] also noted that a preoperative Doppler examination is mandatory when considering the use of DMA flaps. As we mentioned earlier, in our study, the Doppler ultrasound was performed before every operation and the success rate of the operation was also high.…”
mentioning
confidence: 99%